LINGUOCULTURAL ANALYSIS OF CONNOTATIVE UNITS RELATED TO ENDEARMENT IN THE UZBEK LANGUAGE - Kholmamatova Sarvinozhon Abduvali qizi (Bright Mind Publishing, 2025)
Terms of endearment manifest diversely across languages and cultures, reflecting sociocultural, geographical, and emotional contexts of their speakers. This study examines Uzbek endearments in comparison with other linguistic traditions, highlighting their semantic, pragmatic, and psycholinguistic dimensions. Zoonymic, astronimic, sweet/tasty, body-part, and abstract-concept-based endearments are analyzed to demonstrate their role in expressing affection, reinforcing social bonds, and preserving cultural values. The research employs comparative and descriptive methodologies, integrating historical, literary, and contemporary linguistic sources. Findings indicate that Uzbek endearments not only convey love and tenderness but also serve as cultural markers, pedagogical instruments, and carriers of intergenerational emotional heritage.
Keywords: Terms of endearment; Uzbek language; affective linguistics; linguocultural semantics; diminutives; psycholinguistics; comparative linguistics.